The coming age of evangelical Protestantism - Berryman, Phillip (Report on the Americas, 1994)
Observers have been slow to acknowledge the significance of evangelical growth in Latin America. The new reality is that across the region, the number of active Protestant churchgoers is comparable to that of practicing Catholics. (NACLA)